Wage discrimination against immigrants in Austria? - Helmut Hofer; Gerlinde Titelbach; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2014)
This paper analyses wage discrimination against immigrants in Austria using combined information from the labor force surveys and administrative social security data. We find that immigrants experience a wage disadvantage of 15 percentage points compared to natives. However, a substantial part of the wage gap can be explained by differences in human capital endowment and job position. Decomposition methods using quantile regressions show larger discrimination in the upper part of the wage distribution. Moreover, we do not find any evidence for wage assimilation of immigrants in Austria.
Keywords: 330